2013
DOI: 10.1186/1472-6882-13-211
|View full text |Cite
|
Sign up to set email alerts
|

The anti-shigellosis activity of the methanol extract of Picralima nitida on Shigella dysenteriae type I induced diarrhoea in rats

Abstract: BackgroundPicralima nitida Stapf (Apocynaceae) is a medicinal plant used traditionally in Cameroon to cure various ailments such as gastrointestinal disorders and dysentery. This study reports the in vitro and in vivo anti-shigellosis activity of the methanol extract of this plant on rats.MethodsThe antimicrobial activity of the extract against pathogenic strains was evaluated using the disc diffusion assay and broth microdilution method. After oral administration of a suspension of Shigella dysenteriae type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…In vitro antimicrobial study showed an inhibitory activity of extract against Sd1 growth. Minimal inhibitory concentration and MBC values of O barrelieri aqueous extract were high compared to norfloxacin MIC value (0.5 to >256 μg/L), although they are closer to those reported for other plant extracts, eg, 0.8 mg/mL with the methanol extract of Picralima nitida , 1.17 mg/mL with aqueous extract of Mallotus oppositifolium , and 3.5 mg/mL with aqueous ethanol extract of Euphorbia prostrata ait . These results are probably due to the fact that this crude extract might contain less active compounds against this bacterial strain.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In vitro antimicrobial study showed an inhibitory activity of extract against Sd1 growth. Minimal inhibitory concentration and MBC values of O barrelieri aqueous extract were high compared to norfloxacin MIC value (0.5 to >256 μg/L), although they are closer to those reported for other plant extracts, eg, 0.8 mg/mL with the methanol extract of Picralima nitida , 1.17 mg/mL with aqueous extract of Mallotus oppositifolium , and 3.5 mg/mL with aqueous ethanol extract of Euphorbia prostrata ait . These results are probably due to the fact that this crude extract might contain less active compounds against this bacterial strain.…”
Section: Discussionsupporting
confidence: 66%
“…In vitro antimicrobial study showed an inhibitory activity of extract Picralima nitida, 41 1.17 mg/mL with aqueous extract of Mallotus oppositifolium, 32 and 3.5 mg/mL with aqueous ethanol extract of Euphorbia prostrata ait. 31 These results are probably due to the fact that this crude extract might contain less active compounds against this bacterial strain.…”
Section: Discussionmentioning
confidence: 98%
“…However, if the interpretation of Kouitcheu et al, (2013) was taken into account, only nine extracts had MIC higher than 8 mg/mL on some germs, which means that all the other extracts of C. bernieri used showed antimicrobial activities. All the extracts had bactericidal action (MBC/MIC ≤ 4) in certain bacteria and bacteriostatic action (MBC/MIC >) 4) in other ones.…”
Section: Discussionmentioning
confidence: 99%
“…For Dalmarco et al (2010), for crude extracts and fractions, a MIC lower than 100 µg/mL was considered as an excellent effect, from 100 to 500 µg/ml as moderate, from 500 to 1000 µg/mL as weak, and over 1000 µg/ml as inactive. According to Kouitcheu et al (2013), when a crude extract was used, the MIC values of 8 mg/mL or below against any microorganism tested was considered as active.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fruits are used for the management of painful menstruation and disorder of the gastrointestinal tract [12,16]. Pharmacological investigations have proved that this plant also possesses anti-plasmodial [17], anti-diarrheic [18,19], anti-diabetic [20], analgesic [21], opioid [22], antimicrobial [23,24], antiinflammatory [21,25], anti-pyretic [26], trypanocidal [27], anti-Shigellosis [28], as well as anti-leishmanial [29] potencies. Despite the vast ethnomedical and scientific reports on the therapeutic efficacy of this plant, detailed toxicological studies and research observations associated this plant with some level of toxicity especially in higher doses and in immunecompromised animal subjects [14,30,31].…”
Section: Introductionmentioning
confidence: 99%